Optimizing Polymer-Stabilized Raw Earth Composites with Plant Fibers Reinforcement for Historic Building Rehabilitation - Souad Menadi; Yazid Hadidane; Mohammed Benzerara; Messaoud Saidani; Morteza Khorami; Redjem Belouettar; Fayçal Slimani; Nadia Gouider; Souhila Rehab-Bekkouche (Buildings, 2023)
This research focuses on the optimization of formulation, characterization, and damage analysis of plant fiber-reinforced polyester resin composites (jute and date palm). To better understand the characteristics and mechanical behavior of these materials, this study investigates the influence of resin content and plant fibers on the physico-mechanical behavior of the resin composites. Resinous composites consisting of polyester resin and raw earth were studied using a novel formulation based on an empirical method that follows the principle of earth saturation with polyester resin. Saturation was achieved with a 28% content of polyester resin, which appeared to be an optimal blend for the earth–resin composite. Plant fibers were randomly incorporated as reinforcement in the composites at various percentages (1%, 2%, and 3%) and lengths (0.5 cm, 1 cm, and 1.5 cm). Mechanical tests including bending, compression, and indentation were conducted to evaluate the mechanical properties of the composites. Analysis of fracture morphology revealed that the deformation and rupture mechanisms in bending, compression, and indentation of these composites differ from those of traditional concrete and cement mortar. The obtained results indicate that the composites exhibit acceptable performance and could be favorably employed in the rehabilitation of historic buildings.